2010
DOI: 10.4314/ijbcs.v4i1.54236
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance of broiler chicks fed Aspergillus niger- fermented Terminalia catappa seed meal-based diet

Abstract: Forty-five, day-old broiler chicks with an initial average weight of 30.25±2.40 g were divided into three groups of fifteen animals each. The first group was placed on soybean-based (control) diet; the second group on raw (unfermented) T. catappa seed meal-based diet; and the third on A. niger-fermented T. catappa seed meal-based diet, for seven (7) weeks. Feed intake, feed conversion ratio, average weekly body weight gain and mortality were monitored. Though significantly lower (p<0.05) than the control, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
6
25
0
Order By: Relevance
“…Furthermore, the decrease in the total hemoglobin in the diabetic animals treated with distilled water may be a consequence of reaction between excess glucose in the blood of diabetic animals with hemoglobin to form glycosylated hemoglobin (Sheela and Augusti, 1992). Reduction in hemoglobin may be accompanied by a fall in the red blood cell count and packed cell volume (Moss, 1999;Muhammad and Oloyede, 2009). The findings in the present study are similar to that reported elsewhere (Mansi, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the decrease in the total hemoglobin in the diabetic animals treated with distilled water may be a consequence of reaction between excess glucose in the blood of diabetic animals with hemoglobin to form glycosylated hemoglobin (Sheela and Augusti, 1992). Reduction in hemoglobin may be accompanied by a fall in the red blood cell count and packed cell volume (Moss, 1999;Muhammad and Oloyede, 2009). The findings in the present study are similar to that reported elsewhere (Mansi, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Previous comparison of the biological value of raw T. catappa with that of soy protein showed that the protein was poorly digested and utilized. Aspergilus niger fermentation however improved its performance significantly (Muhammad and Oloyede 2004;Muhammad and Oloyede 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It may also show that the drug lacked erythropoietic potentials. Very low levels of red blood cells, haemoglobin and haematocrits can predispose to anaemia (Muhammad and Oloyede, 2009). This might be that the oxygen carrying capacity of the blood and the amount of oxygen delivered to the tissues were reduced by the drug administered.…”
Section: Discussionmentioning
confidence: 99%